2012
DOI: 10.1002/jhm.1934
|View full text |Cite
|
Sign up to set email alerts
|

Sleep rounds: A multidisciplinary approach to optimize sleep quality and satisfaction in hospitalized patients

Abstract: BACKGROUND: Poor sleep has adverse affects on heath, yet few studies have addressed the goal of improving sleep among hospitalized patients. We evaluated the effectiveness of a sleep-promoting intervention on the quality and quantity of sleep among inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 25 publications
3
52
0
2
Order By: Relevance
“…There are both intrinsic and extrinsic factors that contribute to development of SWD during hospitalization 3,[18][19][20] . Intrinsic factors vary by patient, but can include primary medical illness, delirium, psychiatric co-morbidity (anxiety, depression, post-traumatic stress), pre-existing SD and physical pain or discomfort 1,2,21,22 . Pain and discomfort are generally the most frequently cited causes of SWD during hospitalization 1 .…”
Section: Sleep Wake Dysfunction In Hospitalized Patientsmentioning
confidence: 99%
See 4 more Smart Citations
“…There are both intrinsic and extrinsic factors that contribute to development of SWD during hospitalization 3,[18][19][20] . Intrinsic factors vary by patient, but can include primary medical illness, delirium, psychiatric co-morbidity (anxiety, depression, post-traumatic stress), pre-existing SD and physical pain or discomfort 1,2,21,22 . Pain and discomfort are generally the most frequently cited causes of SWD during hospitalization 1 .…”
Section: Sleep Wake Dysfunction In Hospitalized Patientsmentioning
confidence: 99%
“…Environmental noise can be due to equipment/alarms, medical staff, or hospital roommates. Roommates are commonly reported as the most disturbing factor for sleep 1 . A study evaluating acceptable environmental noise levels found that daytime noise of 59 decibel A (dBA) and nighttime noise of 50.5 dBA did not result in SWD.…”
Section: Sleep Wake Dysfunction In Hospitalized Patientsmentioning
confidence: 99%
See 3 more Smart Citations